INFLUENCE OF THERMOPHYSICAL PROPERTIES OF THE METAL OF POLYMER COMPOSITE MATERIALS ON WEAR RESISTANCE - Khimko, Marharyta; Khimko, Andrii; Mnatsakanov, Rudolf; Mikosianchyk, Oksana (Problems of Friction and Wear, 2024)
Metal-polymer composite materials were tested at ambient temperatures of 20 and 60 °C. The most modern composite wear-resistant materials used in mechanisms as sliding bearings were used. The relevance of the tests is determined by the application of worldwide trends to mechanisms without maintenance for the entire life cycle. The influence of temperature on the wear resistance of metal-polymer composite materials that can be used in aviation spherical plane bearings is determined. It was determined that heat generation caused by both the friction process and dynamic load as a result of reverse motion has the greatest influence on the wear intensity. Increasing the test temperature affects polymer composite materials to a greater extent than metal-polymer tape. At this stage, a significant role in wear resistance is played with the ability of the material to dissipate heat, which occurs in the contact zone from reversible sliding. It has also been established that the carbon fabric of the Fluroglide material can withstand higher temperatures than the babbitt of the metal-polymer tape. A key role in the durability of spherical plane bearings that work in non-standard temperatures will be played by the composite materials design selection and the polymer materials themselves for specific operating conditions.